A Prognostic Survival Model of Pancreatic Adenocarcinoma Based on Metabolism-Related Gene Expression - Xie, Lin-ying; Huang, Han-ying; Fang, Tian; Liang, Jia-ying; Hao, Yu-lei; Zhang, Xue-jiao; Xie, Yi-xin; Wang, Chang; Tan, Ye-hui; Zeng, Lei (Frontiers in Genetics, 2022)
Accurately predicting the survival prospects of patients suffering from pancreatic adenocarcinoma (PAAD) is challenging. In this study, we analyzed RNA matrices of 182 subjects with PAAD based on public datasets obtained from The Cancer Genome Atlas as training datasets and those of 63 subjects obtained from the Gene Expression Omnibus database as the validation dataset. Genes regulating the metabolism of PAAD cells correlated with survival were identified. Furthermore, LASSO Cox regression analyses were conducted to identify six genes (XDH, MBOAT2, PTGES, AK4, PAICS, and CKB) to create a metabolic risk score. The proposed scoring framework attained robust predictive performance, with two-year survival areas under the curve (AUCs) of 0.61 in the training cohort and 0.66 in the validation cohort. Compared with the subjects in the low‐risk cohort, subjects in the high‐risk training cohort presented a worse survival outcome. The metabolic risk score increased the accuracy of survival prediction in patients suffering from PAAD.